Research guide for water-energy-food nexus analysis - Ringler, Claudia; Mondal, Md. Hossain Alam; Paulos, Helen Berga; Mirzabaev, Alisher; Breisinger, Clemens; Wiebelt, Manfred; Siddig, Khalid; Villamor, Grace; Zhu, Tingju; Bryan, Elizabeth (International Food Policy Research Institute, 2018)
The project titled “The Water-Energy-Food Nexus: Global, Basin and Local Case Studies of Resource Use Efficiency under Growing Natural Resource Scarcity“ (2015-2018), which was supported by the Federal Ministry for Economic Cooperation and Development, Germany, and was undertaken as part of the CGIAR Research Program on Water, Land and Ecosystems. The project set out to develop research methodologies and insights globally as well as for the Eastern Nile Technical Regional Organization (ENTRO) of the Nile Basin Initiative (NBI) and Egypt, Ethiopia and Sudan to support efforts for enhanced water, energy and food security and environmental sustainability. The toolkit describes both qualitative and quantitative methods that have been used in the research project. It is not meant to be an exhaustive list of information and tools related to the analysis of the water, energy and food (WEF) nexus. The overall focus of the tools has been on economic analysis of the linkages across water, energy and food--to complement other studies and method developments that focus on biophysical linkages across the WEF nexus. The toolkit is aimed, primarily, at researchers interested in the analysis of the water, energy and food nexus. However, the studies summarized here also provide insights for practitioners implementing Nexus projects.